Exploring Students’ Perspectives on Sufism and Tarekat in Islamic Education - Fahrudin Fahrudin; Munawar Rahmat; M. Wildan Bin H.M. Yahya; Makhmud Syafei; Maman Abdurrahman (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This study examines the perspectives of Islamic master's students in Bandung, Indonesia, towards sufism and tarekat, sufi orders (Arab: ṭarȋqah). The objective is to analyze graduates' beliefs regarding the influence of foreign practices on sufism and their explanations of the controversial doctrines associated with tarekat. Utilizing a qualitative approach, eight respondents from two universities, who demonstrated high proficiency in the sufism course, were selected. The research employed documentation studies and in-depth interviews as primary techniques. Assessments were conducted before and after the sufism course to gauge respondents' attitudes towards the central tenets of sufism and tarekat. The results indicated significant shifts in viewpoints, with the majority initially holding opposing perspectives that evolved positively after the course. Many graduates embraced tarekat under the guidance of a murshîd (spiritual guide) and accepted doctrines such as żikr-tarekat, talqȋn-żikr, ma'rifat, and waḥdat al-wujûd. The study concludes that Sufism lectures have a constructive impact on fostering religious moderation among students, effectively countering the negative narrative propagated by the Salafi campaign against sufism and tarekat. The findings highlight the importance of conducting Sufism lectures in Islamic master's programs, emphasizing their effectiveness in shaping graduate students' attitudes towards tarekat.